A proposed scenario to activate volunteer efforts for youth in dealing with societal crises - Khalifa, Heba Ahmed; Al-Salami, Rana Saad Allah (Journal of Humanities & Social Sciences, 2021)
The study aimed to achieve a general goal: to stand on activating the volunteer efforts of youth to deal with societal crises by identifying the motives of volunteer work among youth in times of community crises, as well as identifying the areas of volunteer work carried out by young people in times of community crises, and also identifying the positive effects The consequences of undertaking volunteer work for youth in times of community crises, as wells identifying the difficulties that limit volunteer work for youth in times of community crises, in order to reach proposals to contribute to activating volunteer work for youth in times of community crises. The two researchers used the method of social sample survey of volunteers in the Kingdom of Saudi Arabia, where their number reached (104), and the questionnaire was distributed electronically and the two researchers used multiple statistical transactions, and the results of the study indicated that their motives for volunteering to help them build new social relationships, and that one of the most prominent areas of volunteer work is participation in awareness and education campaigns, and one of the most important effects The positivity for their volunteer work is to strengthen their connection to the problems of their society, which contributes to the development of a sense of social responsibility they have, and the lack of special programs to train volunteers before assigning them to volunteer work was one of the most prominent difficulties, while one of the most important proposals was to instill a love of volunteer work in the early stages of life for young people, as it enhances their desire To participate in volunteer work.